Analisis Perancangan Aplikasi Layanan Konseling Individual Berbasis Aplikasi Website Di SMPN 2 Merangin - Carla Dewi (Jurnal Pendidikan Islam, 2021)
guidance and counseling which is part of education as a process of providing assistance to individuals (counselees) in dealing with problems, which is carried out through various kinds of services. E-counseling is an effective and efficient way of distance counseling between counselors and clients to help with problems related to personality development and client's life, letters or writing on the internet. The purpose of Website-based Guidance and Counseling is to provide services to students via the web on academic, socio-personal, career issues and develop students' full potential, adapt to the environment, how to overcome difficulties and obstacles in the student environment.The development model used in this study uses the ADDIE Branch theory research model. The feasibility assessment by media experts obtained an average score of 5.0. When converted into a percentage, the figure is obtained 100%, so this product is included in the category of interpretation of "Very Appropriate" and effective. The feasibility assessment by the material expert obtained an average score of 4.70. When converted into a percentage, the figure is 94%, so this product is included in the category of interpretation of "Very Appropriate" and effective. The feasibility assessment by 36 students obtained an average score of 4.65. When converted into a percentage, the figure is 93%, so this product is included in the category of interpretation of "Very Appropriate" and effective.